Notas sobre a redescoberta de Hevea camporum Ducke. - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1961)
The original herbarium material upon which the species Hevea camporum Ducke was based is incomplete and the species has until recently been considered as a possible variety of H. pauciflora (Spr. ex Bth.) M. Arg. New collections from the "cmpos" of the Cururu river (upper Tapajós) River region) demonstrate the validity of Ducke´s species and permit an amplification of the original description. Hevea camporum Ducke is one of the most distinct species of the genus. It may be easily recognized by the following characteristics: plant dwarf (2m tall) on sandstone "campo" soils; leaves very small, leaflets with a small callosity at the tip of the midvein; ring of dormancy ("short-shoot" of seibert) (7) inconspicuous; inflorescence short, pubescent, as is H. pauciflora; male buds very acuminate, twisted to the tip; calyx lobes very long, linear, plicate; anthers commonly 7 in two whorls; femele receptacle not swollen, ovary hairy; capsulke very small, with minute seeds and violent dehiscense. The closest species appears to be H. rigidifolia (Bth.) M. Arg.
Keywords: Hevea camporum; Euphorbiaceae